The Effect of Stakeholder-Associated Risks in Mega-Engineering Projects: A Case Study of a PPP Airport Project - Aladag, Hande; Isik, Zeynep (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
Mega-engineering projects in the construction industry are generally carried out by public-private partnership models with the participation of different stakeholders. This paper aims to identify the effect of stakeholder-associated risks on the success of mega-engineering projects. Therefore, the risks were determined and then validated by focus discussions. Afterwards, an illustrative case study was presented to better understand the effects. Finally, a fuzzy analytical hierarchy process method was used to prioritize the identified risks. The prominent risks were found to include improper partner selection, inadequate relationships with employer, and incompetent contractor selection. Engineering managers need to work in close coordination with all members of the project. To better manage projects, engineering managers are expected to be familiar with the concepts of project risk management, because effective project risk management has a direct and positive effect on project management performance. Professionals in the field of engineering management can benefit greatly from the findings of this study by using it as a baseline for coordinating the relationships in multistakeholder organizational structures and analyzing stakeholder-associated risks throughout their projects.
Keywords: Stakeholders; Companies; Risk management; Investment; Law; Raw materials; Build-operate-transfer (BOT); case study; construction industry; fuzzy analytical hierarchy process (FAHP); public-private partnership (PPP); stakeholder-associated risk; PUBLIC-PRIVATE PARTNERSHIP; CRITICAL SUCCESS FACTORS; ENVIRONMENTAL-IMPACT ASSESSMENT; ANALYTIC NETWORK PROCESS; DECISION-SUPPORT; INFRASTRUCTURE PROJECTS; FUZZY-LOGIC; ALLOCATION; PERSPECTIVE; Business & Economics; Engineering